Potensi, Tingkat Pemanfaatan dan Keberlanjutan Ikan Tembang (Sardinella spp.) di Perairan Selat Malaka, Kabupaten Serdang Bedagai, Sumatera Utara - Rina Sari Lubis; Miswar Budi Mulya; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2013)
Tembang fish (Sardinella spp.) is a small pelagic fish, which live inschooling. This fish can be caught using drift gill net gear, purse seine, handlinesand payang. The purpose of this study was to determine the potential ofsustainability with optimum fishing effort, utilization rates and insistence,sustainability and management of fish resources in Malacca Strait. The analysisof secondary data from 2008 to 2012 obtained from the Department of Marineand Fisheries Serdang Bedagai regency, and primary data obtained by performeda questionnaire related to the sustainability of tembang fish.The potential prediction performed with Fox model. The result shown thatMSY was 5.930,582 tons/year and optimum effort was 22.466 trips/year. Averageutilization rate of 44,95%, with an average rate of 77,26% insistence, whileallowable catch 4.744,465 tons/year. The sustainability of tembang fish,dimensional the ecological, technologies and institutions into unsustainablecategory. While economic and social dimensions included the category ofsustainable. The management efforts was by setting fishing season, the selectivityof fishing gear, prohibition of fishing gear and quota restrictions arrest.Keywords: Malacca Strait, Potential, Utilization, Sustainability, Sardinella spp.